Keterkaitan Panhisterektomi dan Suplemen 1,25- Dihidroksivitamin D3 dengan Risiko Urolitiasis pada Tikus (CORRELATION BETWEEN PANHISTERCTOMY AND 1.25-DIHYDROXYVITAMIN D3 SUPPLEMENTATION ON RATS UROLITHIASIS RISK) - ., Hartiningsih; Anggraeni, Devita; Widiyono, Irkham; Wuryastuti, Hastari (Jurnal Veteriner, 2013)
The objective of this research was to study the correlation of panhisterectomy and supplement 1.25-dihydroxyvitamin D3 on urolithiasis risk in Wistar rats. Twenty female Wistar rats at 8 weeks of age, weredivided into four groups (control fed standard diet, control fed standard diet+1,25-dihydroxyvitamin D3 supplement, panhisterectomy fed standard diet and panhisterectomy fed standard diet +1,25-dihydroxyvitamin D3 supplement). Eleven weeks after treatment, each of rats was placed into individualmetabolic cage for balance study for a week. From day 4 to 11 of the balance study, every morning theremaining food, feces, and urine were collected and recorded for calcium (Ca) analysis. At the end ofbalance study, blood samples were taken from canthus retroorbitalis medialis for estrogen analysis. Theresults showed urinary and fecal Ca excretions were not significantly different compared to the controlgroup. Calcium consumption was significantly higher (P<0.05) in panhisterectomized rats compared withthose in control rats. While, estrogen in panhisterectomized group was not significantly different to thosein control rats. Calcium urinary and Ca consumption in rats consuming 1,25-dihydroxyvitamin D3 supplement were significantly higher (P<0.05) compared with those in without 1,25-dihydroxyvitamin D3 supplementation, but Ca excretion in feses was not significantly different. Estrogen in rats consuming1.25-dihydroxyvitamin D3 supplement was significantly lower (P<0.05) compared with the rats that without1,25-dihydroxyvitamin D3 supplemention. It can be concluded that panhisterectomy does not seem to affecturolithiasis risk, while 1,25-dihydroxyvitamin D3 supplement may affect urolithiasis risk. There is likelyno association between panhisterectomy and 1.25-dihydroxyvitamin D3 supplementation on urolithiasisrisk in Wistar rats.
Keywords: Panhisterectomy, 1.25-dihydroxyvitamin D3, Ca urinary, urolithiasis